Teledermatology in Developing Countries (Chances and Obstacles) - Günter Burg (Nepal Journal of Dermatology, Venereology & Leprology)
Telemedicine has started to be a serious tool for the improvement of healthcare in rural areas of poor developing but also in rich industrial countries. Teledermatology as a subspeciality of telemedicine is particularly suitable for diagnosing and monitoring diseases over distance. However some dermatoses are less, others are more suitable for remote management. The technologies used provide big chances if the many obstacles can be overcome.